f ( x ) = 1 − 2 1 cos x + 2 × 4 1 × 3 cos 2 x − 2 × 4 × 6 1 × 3 × 5 cos 3 x ⋯ .
⌊ 1 0 0 0 0 × f ( 3 π ) ⌋ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same except the fact that I considered substituting 2 e i n x + e − i n x for c o s ( n x ) and then little bashing.
This problem is underrated!
We have:
1 + x 1 = 1 − 2 1 x + 2 ∗ 4 1 ∗ 3 x 2 − 2 ∗ 4 ∗ 6 1 ∗ 3 ∗ 5 x 3 . . .
The required expression is then the real part of what one gets upon making the substitution
x = e i x
Let z = 1 + e i x 1 .
Then,
ℜ ( z ) = 2 z + z ˉ
Where z ˉ = 1 + e − i x 1
This upon further simplification gives:
ℜ ( z ) = c o s ( 2 x ) 2 c o s 2 ( 4 x )
Now just plug in x = 3 π .
Though I made this problem incorrect , but
Making the substitution does'nt give that expression , you should show whole solution , many may can't understand.
f ( x ) = 1 − 2 1 c o s x + 2 . 4 1 . 3 c o s 2 x − 2 . 4 . 6 1 . 3 . 5 c o s 3 x ⋯ .
g ( x ) = − 2 1 s i n x + 2 . 4 1 . 3 s i n 2 x − 2 . 4 . 6 1 . 3 . 5 s i n 3 x ⋯ .
f ( x ) + i ( g ( x ) ) = 1 − 2 1 ( cos ( x ) + i sin ( x ) ) + 2 . 4 1 . 3 ( cos ( 2 x ) + i sin ( 2 x ) ) − 2 . 4 . 6 1 . 3 . 5 ( cos ( 3 x ) + i sin ( 3 x ) ) ⋯
f ( x ) + i ( g ( x ) ) = 1 − 2 1 ( e i θ ) + 2 . 4 1 . 3 ( e i θ ) 2 − 2 . 4 . 6 1 . 3 . 5 ( e i θ ) 3 ⋯
= 1 + 1 . 2 1 e i θ + 1 . 2 2 1 . 2 3 × ( e i θ ) 2 − 1 . 2 . 3 2 1 . 2 3 . 2 5 × ( e i θ ) 3 + . . . . . . .
= 1 + 1 . 2 1 e i θ + 2 ! 2 1 . ( 1 + 2 1 ) × ( e i θ ) 2 + 3 ! 2 1 . ( 1 + 2 1 ) . ( 2 + 2 1 ) × ( e i θ ) 3 + . . . . . . .
Now yours equation comes to play,
1 + x 1 = 1 − 2 1 x + 2 ∗ 4 1 ∗ 3 x 2 − 2 ∗ 4 ∗ 6 1 ∗ 3 ∗ 5 x 3 . . .
thus ,
= 1 + e x 1
Nicely founded real part, this part made me wrong
Log in to reply
Perhaps this is too late a reply but I did mention that it is the r e a l p a r t of what one gets after making the substitution. My apologies if it was still unclear...
since the denominator is undefined for cos(π/2)=0 your last expression in a square root is ambiguous.
Consider the binomial expansion of 1 + x 1 :
( 1 + x ) − 2 1 1 + e x i 1 ℜ ( 1 + e x i 1 ) = 1 − 2 1 x + 2 ! 2 1 × 2 3 x 2 − 3 ! 2 1 × 2 3 × 2 5 + ⋯ = 1 − 2 1 x + 2 × 4 1 × 3 x 2 − 2 × 4 × 6 1 × 3 × 5 x 3 + ⋯ = 1 − 2 1 e x i + 2 × 4 1 × 3 e 2 x i − 2 × 4 × 6 1 × 3 × 5 e 3 x i + ⋯ = 1 − 2 1 cos x + 2 × 4 1 × 3 cos 2 x − 2 × 4 × 6 1 × 3 × 5 cos 3 x + ⋯ By Euler’s formula: e θ i = cos θ + i sin θ where ℜ ( ⋅ ) denotes the real part of a complex number.
⟹ f ( x ) f ( 3 π ) = ℜ ( 1 + e x i 1 ) = ℜ ( 1 + e 3 π i 1 ) = ℜ ⎝ ⎛ 2 3 + 2 3 i 1 ⎠ ⎞ = ℜ ⎝ ⎜ ⎜ ⎛ 3 ( 2 3 + 2 1 i ) 1 ⎠ ⎟ ⎟ ⎞ = ℜ ( 4 3 e − 1 2 π i ) = ℜ ( 4 3 cos 1 2 π − i sin 1 2 π ) = = 4 3 cos 1 2 π ≈ 0 . 7 3 3 9
Therefore, ⌊ 1 0 0 0 0 f ( 3 π ) ⌋ = 7 3 3 9 .
Problem Loading...
Note Loading...
Set Loading...
First Of All We Assume An Equation With Negative Index
( 1 + x ) − n
Where n ϵ R +
( 1 + x ) − n = 1 − n x + 2 n ( n + 1 x 2 − 1 . 2 . 3 n ( n + 1 ) ( n + 2 ) ⋯
And Comparing With the Given Equation,
1 − 2 1 c o s x + 2 . 4 1 . 3 c o s 2 x − 2 . 4 . 6 1 . 3 . 5 c o s 3 x ⋯
We Get,
n x = 2 1 c o s x
And
2 n ( n + 1 ) x 2 = 2 . 4 1 . 3 c o s 2 x
Solving Them We Get
n = 2 1
And
Substituting In The Third Term To Verify The Consistency.
Then The Required Solution Is
( 1 + e i θ ) 2 − 1 = 1 − 2 1 e i θ + 2 . 4 1 . 3 ( e i θ ) 2 − 2 . 4 . 6 1 . 3 . 5 ( e i θ ) 3 ⋯
Using De Moivre's formula That
( cos x + i sin x ) α = cos ( α x ) + i sin ( α x )
We Get,
( 1 + e i θ ) 2 − 1 = 1 − 2 1 ( cos ( x ) + i sin ( x ) ) + 2 . 4 1 . 3 ( cos ( 2 x ) + i sin ( 2 x ) ) − 2 . 4 . 6 1 . 3 . 5 ( cos ( 3 x ) + i sin ( 3 x ) ) ⋯
R e ( 1 + e i θ ) 2 − 1 = 1 − 2 1 c o s x + 2 . 4 1 . 3 c o s 2 x − 2 . 4 . 6 1 . 3 . 5 c o s 3 x ⋯
Where Re is the Real Part Of the Complex Number
So
f ( x ) = R e ( 1 + e i θ ) 2 − 1
f ( 3 π ) = R e ( 1 + e i 3 π ) 2 − 1
Upon Simplifying The Above Equation We get,
f ( 3 π ) = c o s ( 6 π ) 2 c o s 2 ( 1 2 π )
f ( 3 π ) = 3 4 − 1 . cos ( 1 2 π ) = 0 . 7 3 3 9 4 4 ⋯